The consequences of possession / edited by Eric Descheemaeker. - Descheemaeker, Eric, 1977- (Edinburgh studies in law, 2014)
Possession is a topic which has been researched for centuries, yet there is a surprising dearth of comparative materials and also very little available in English about the law of non-Anglophone jurisdictions. Leaving aside the question of what possession is, this analysis concerns itself with the law's response to 'possession'. The volume comprises contributions from some very distinguished scholars from the civilian tradition (Germany, Italy) as well as the common law (England) and mixed legal systems (Quebec, Scotland, South Africa). Key Features * Written by an international set of contributors from jurisdictions including Germany, Italy, England, Quebec, Scotland and South Africa *Looks at common law, civil law and combined jurisdictions *The first synthesis of theory on the subject of possession * The Contributors: Craig Anderson, Lecturer in Law at Robert Gordon University, Aberdeen Raffaele Caterina, Professor of Law at the University of Turin Eric Descheemaeker, Lecturer in European Private Law at the University of Edinburgh Simon Douglas, CUF Lecturer in the University of Oxford and Fellow and Tutor in Law at Jesus College, Oxford Yaëll Emerich, Associate Professor at the Faculty of Law, McGill University, Montreal Robin Hickey, Senior Lecturer in Law at Queen's University Belfast Duard Kleyn, Professor of Law at the University of Pretoria Lena Kunz, Post-doctoral Researcher at the Institute of Legal History, University of Heidelberg Thomas Rüfner, Professor of Law at the University of Trier and Judge on the Court of Appeal in Koblenz